Beyond September 11 and the Enlightened Moderation: Situating Trajectories of Islamic Reform in Pakistan in the Historical Context - Amin, Husnul (Islamic Studies, 2016)
This paper defines the historical context within which the religio-political movements of today’s Pakistan are situated. The advent of various events in the nineteenth and early twentieth centuries, the emergence of numerous intellectual trends in response to colonial conditions, and the multi-layered deprivations of the Muslims in India are of paramount significance. These events and trends shaped the proliferation of other numerous intellectual and social trajectories in contemporary Pakistan. My research deviates from the general trend prevalent among the academic community that attempts to understand the diverse social and intellectual manifestations of Islamic activism in the light of violence on the one hand, and an enlightened moderation project on the other. A historical account, in a comparative fashion, of the various Islamic responses in the nineteenth and twentieth centuries British colonial India reveals that the contemporary social expressions and intellectual movements directed at reform are historically rooted and not just reactionary outbursts.